2019
DOI: 10.1111/papr.12751
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcome of Acute Sacral Nerve Stimulation in Functional Anorectal Pain

Abstract: Background Sacral nerve stimulation (SNS) has revolutionized the management of certain intractable cases of fecal and urinary incontinence; however, the management of functional anorectal pain (FAP) has been addressed in only a few studies. Objective The aim of this study was to evaluate the treatment effect of SNS in improving FAP symptoms. Methods A total of 120 patients with FAP who had undergone temporary SNS probe placement were investigated at Qianfoshan Hospital between January 2014 and December 2016. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…The total effectiveness rate was 96.7%, and the median VAS score reduced from 8 to 3 one year after treatment. Patients also had significant improvement on anal maximum contraction pressure and anal rest pressure (73). Similarly, Falletto et al (74) reported that in 12 patients with idiopathic anal pain, VAS score significantly improved from 8.2 ± 1.7 to 2.2 ± 1.3 (P < 0.001) and 36 Item Short Form Health Survey (SF-36) physical component scores increased from 26.27 ± 5.65 to 38.95 ± 9.08 (P < 0.02) after sacral nerve stimulation during a mean follow-up of 15 months.…”
Section: Inguinal/genital/pelvic Painmentioning
confidence: 91%
See 1 more Smart Citation
“…The total effectiveness rate was 96.7%, and the median VAS score reduced from 8 to 3 one year after treatment. Patients also had significant improvement on anal maximum contraction pressure and anal rest pressure (73). Similarly, Falletto et al (74) reported that in 12 patients with idiopathic anal pain, VAS score significantly improved from 8.2 ± 1.7 to 2.2 ± 1.3 (P < 0.001) and 36 Item Short Form Health Survey (SF-36) physical component scores increased from 26.27 ± 5.65 to 38.95 ± 9.08 (P < 0.02) after sacral nerve stimulation during a mean follow-up of 15 months.…”
Section: Inguinal/genital/pelvic Painmentioning
confidence: 91%
“…The management of functional anorectal pain remains a challenge, and SNM treatment was addressed in several studies. In a prospective study by Rongqing et al (73), a total of 120 patients received temporary SNM at the S3 nerve root (2 Hz, 1.50 mA, 0.10 ms). Of these, 75 patients were pain free, 41 improved, and 4 had an ineffective outcome.…”
Section: Inguinal/genital/pelvic Painmentioning
confidence: 99%
“…Qualitative analysis of the effect of SNM on CPP Six studies were not included in quantitative analysis. 14,21,26,[28][29][30] Two hundred and sixty patients with CPP across the studies underwent a test phase, 96 were implanted with IPGs. One study did not report IPG implantation, resulting of an implantation rate of 66.7% across remaining studies.…”
Section: Primary Outcomementioning
confidence: 99%
“…28 A study of short-term SNM demonstrated only a temporary improvement in QoL which was not maintained at follow-up regardless of pain symptoms. 14 Complications There were 189 reported complications in 24 studies comprising 1555 patients (Table 2). The most common complications were pain at the implant site (35 cases, 2.2%) (Clavien-Dindo grade I) followed by infection (23 cases, 1.48%) (grade II-IIIb).…”
Section: Secondary Outcomesmentioning
confidence: 99%
See 1 more Smart Citation